Increased expression of α7nAChR in chronic rhinosinusitis: The intranasal cholinergic anti-inflammatory hypothesis - Cerejeira, Rui; Fernandes, Susana; Pinto Moura, Carla (Auris, nasus, larynx, 2016)
Chronic rhinosinusitis results from a dysfunctional host–environment interaction at the site of interface, in the nose and paranasal sinuses. A parasympathetic-mediated anti-inflammatory reflex is known to have a pivotal role in the control of damage induced by immune response to injury and infection; acetylcholine released by peripheral nerves interacts with nicotinic acetylcholine receptor subunit α7 – α7nAChR – of innate immune cells, inhibiting pro-inflammatory signalling. This work aims to investigate whether cholinergic function is implicated in chronic rhinosinusitis. α7nAChR mRNA and protein levels were measured in nasal biopsy specimens of 14 patients with CRSwNP, 8 with CRSsNP and 10 control subjects, undergoing surgery. Gene expression levels of α7nAChR did not differ between groups; protein expression was significantly higher in CRSwNP than in CRSsNP (p=0.041), and both of these patient groups showed significant higher levels than controls (CRSwNP vs Controls – p=0.001; CRSsNP vs Controls – p=0.041). Elevated α7nAChR protein levels suggest that the cholinergic system is involved in the inflammatory response of chronic rhinosinusitis. This can shed light on both, the disease pathophysiology and the development of future treatment options.